1983
DOI: 10.1016/0014-5793(83)80355-x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine activation of N‐acetylglutamate synthetase in mouse liver

Abstract: N‐Acetyl‐L‐glutamate sythetase catalyzes the synthesis of N‐acetyl‐L‐glutamate, an allosteric and esential activator of carbamoyl‐phosphate synthetase I in the liver of ureotelic animals. The enzyme is activated specifically by arginine. We report here that the sensitivity of the synthetase to activation by arginine increases markedly after intraperitoneal administration to mice of inhibitors of nucleic acid and protein synthesis, including actinomycin D, aurintricarboxylic acid, cycloheximide, emetine and pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We reported that the sensitivity of acetylglutamate synthetase in mouse liver to arginine activation undergoes marked changes after ingestion offood (Kawamoto et al, 1982) and injection of inhibitors of nucleic acid and protein synthesis (Kawamoto & Tatibana, 1983). Correlations between the extent of arginine activation of acetylglutamate synthesis in isolated mitochondria and the sensitivity to arginine activation of acetylglutamate synthetase, extracted from the mitochondria, were also examined (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We reported that the sensitivity of acetylglutamate synthetase in mouse liver to arginine activation undergoes marked changes after ingestion offood (Kawamoto et al, 1982) and injection of inhibitors of nucleic acid and protein synthesis (Kawamoto & Tatibana, 1983). Correlations between the extent of arginine activation of acetylglutamate synthesis in isolated mitochondria and the sensitivity to arginine activation of acetylglutamate synthetase, extracted from the mitochondria, were also examined (Table 1).…”
Section: Resultsmentioning
confidence: 99%